Managers' and Workers' Attitudes Toward Unions in the U.S. and Canada - Saporta, Ishak; Lincoln, Bryan (Relations industrielles / Industrial Relations, 1995)
Current arguments about the causes of differing union density rates in the U.S. and Canada range from Lipset's public opinion hypothesis and differences in labour law, to increased U.S. managerial hostility. We use survey data on managers' and workers' attitudes in the two countries to examine the competing arguments. Using questions that probe opinions toward various aspects of union-firm relations, we find that managers' attitudes in the two countries do not differ. This finding suggests that increased U.S. managerial hostility is not the cause of the divergent unionization rates. U.S. workers are the most militant of the four groups, with Canadian workers in the middle, between managers and U.S. workers. Following literature which suggests that there may be important regional differences, we perform a similar analysis treating the South in the U.S. and Quebec in Canada separately. We find only minimal cross-regional differences.